Transcriptional regulator MarT negatively regulates MarT-regulated motility gene I, a new gene involved in invasion and virulence of Salmonella enterica - Jerez, Sebastián A.; Mora, Aracely Y.; Millanao, Ana R.; Saavedra, Claudia P.; Bucarey, Sergio A.; Mora, Guido C.; Villagra, Nicolás A.; Hidalgo, Alejandro A. (Frontiers in Microbiology, 2024)
The speciation of Salmonella occurred by acquisition of genomic islands from other bacterial species and continued to diverge into subspecies and serovars with diferent range of host. S. enterica serovar Typhimurium (STM) is a generalist pathogen infecting hosts that include birds, mice, and humans, whilst S. enterica serovar Typhi (STY) is a restricted-host pathogen, infecting only humans. Despite their ranges of hosts, STM and STY possess 97-98% identity. Gain of genes by horizontal transference and loss of genes by mutations, are believed essential for differentiation of Salmonella. Salmonella pathogenicity island 3 (SPI-3) is an example combining these two processes. SPI-3 encodes misL and marT, among other genes. In STM, misL is required for gut colonization. Furthermore, protein MarT, positively regulates expression of misL by binding to misL-promoter. On the other hand, in SPI-3 of STY, marT and misL are pseudogenes. Interestingly, the gene t3766 (gene involved in resistance to H2O2) is present only in STY and is negatively regulated when marTSTM is heterologously expressed in STY. Based on the view that MarT might regulate genes implicated in virulence, this work searched for new genes regulated by MarT. In silico searches for possible MarT target genes were performed, and 4 genes were selected for further analysis as they contained at least copies of the consensus MarT-binding sequence in their promoters. Mutating marT in STM or heterologously expressing marTSTM in STY confirmed that MarT negatively regulates ORF STY1408 or STM14_2003, its homologue in STM. STY1408 encodes for a putative protein with homology to methyl accepting chemotaxis proteins, which participate in chemotaxis and motility. Therefore, STY1408 was named mrmI (MarT-regulated motility gene I). Motility assays confirmed that the product of mrmI modulates motility. In addition, in vitro infection of cells with STM and STY mutants in mrmI reduces association with cells at 1, 3 and 24 h postinfection. Oral infection of mice showed that a mrmI null mutant was defective in producing systemic disease. Therefore, we conclude that MarT regulated mrmI, is involved in virulence of Salmonella. While pseudogenization of marT might modulate the fitness of narrow host range STY.